A historical and political epistemology of microbes. (12th July 2020) - D'Abramo, Flavio; Neumeyer, Sybille
Abstract: This article traces the historical co‐evolution of microbiology, bacteriology, and virology, framed within industrial and agricultural contexts, as well as their role in colonial and national history between the end of the 19th century and the first decades of the 20th century. The epistemology of germ theory, coupled with the economic interests of European colonies, has shaped the understanding of human‐microbial relationships in a reductionist way. We explore a brief history of the medical and biological sciences, focusing on microbes and the difficulty of implementing germ theory outside of biology laboratories. Furthermore, we highlight the work of Lynn Margulis, who conceptualized microbes within their ecological contexts. Such research shows the active role microbes play in handling life‐sustaining biological and biochemical processes. We outline how the industrial and technological advancements of the last two centuries not only impacted almost all human societies, but also changed the world on microbial, biological, and geological levels. The narration of these histories is a complex task, and depends on how national, international, and intergovernmental institutions (such as the World Health Organization) conceive of the selective environmental pressures exerted by industry and biotechnological companies.